The Role of Leptin and Adiponectin in Obesity-Associated Cognitive Decline and Alzheimer’s Disease - Forny-Germano, Leticia; De Felice, Fernanda G.; Vieira, Marcelo Nunes do Nascimento (Frontiers in Neuroscience, 2019)
Cross-talk between adipose tissue and central nervous system underlies the increased risk of obese people to develop brain diseases such as cognitive and mood disorders. Detailed mechanisms for how peripheral changes caused by adipose tissue accumulation in obesity impact the central nervous system (CNS) to cause brain dysfunction are poorly understood. Adipokines are a large group of substances secreted by the white adipose tissue to regulate a wide range of homeostatic processes including, but not limited to, energy metabolism and immunity. Obesity is characterized by a generalized change in the levels of circulating adipokines due to abnormal accumulation and dysfunction of adipose tissue. Altered adipokine levels underlie complications of obesity as well as the increased risk for the development of obesity-related comorbidities such as type 2 diabetes, cardiovascular and neurodegenerative diseases. Here, we review the literature for the role of adipokines as key mediators of the communication between periphery and CNS in health and disease. We will focus on the actions of leptin and adiponectin, two of the most abundant and well studied adipokines, in the brain, with particular emphasis on how altered signaling of these adipokines in obesity may lead to cognitive dysfunction and augmented risk for Alzheimer’s disease. A better understanding of adipokine biology in brain disorders may prove of major relevance to diagnostic, prevention and therapy.